The Effect of Business Communication on Employee Performance - Maulani, Galih Abdul Fatah; Zahra, Alfiyah Az; Hamdani, Nizar Alam; Permana, Intan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study discusses an analysis of effect business communication on employee performance at PT JNE Express Across Nations. Researchers used quantitative methods with data collection techniques by questionnaires. Data quality analysis techniques used validity test methods, reliability tests, while hypothesis testing used simple linear regression analysis and t test. Based on the results of research conducted, business communication has a significant effect on employee performance. That way the results of this research can help companies and entrepreneurs to implement the business that is being occupied and can make it easier for future researchers to find the latest references if they have the same variables so that the research can be helped to be more perfect.